Auxiliary strategy for the general and practical synthesis of diaryliodonium(III) salts with diverse organocarboxylate counterions - Miyamoto, Naoki; Koseki, Daichi; Sumida, Kohei; Elboray, Elghareeb E.; Takenaga, Naoko; Kumar, Ravi; Dohi, Toshifumi (Beilstein Journal of Organic Chemistry, 2024)
Diaryliodonium(III) salts are versatile reagents that exhibit a range of reactions, both in the presence and absence of metal catalysts. In this study, we developed efficient synthetic methods for the preparation of aryl(TMP)iodonium(III) carboxylates, by reaction of (diacetoxyiodo)arenes or iodosoarenes with 1,3,5-trimethoxybenzene in the presence of a diverse range of organocarboxylic acids. These reactions were conducted under mild conditions using the trimethoxyphenyl (TMP) group as an auxiliary, without the need for additives, excess reagents, or counterion exchange in further steps. These protocols are compatible with a wide range of substituents on (hetero)aryl iodine(III) compounds, including electron-rich, electron-poor, sterically congested, and acid-labile groups, as well as a broad range of aliphatic and aromatic carboxylic acids for the synthesis of diverse aryl(TMP)iodonium(III) carboxylates in high yields. This method allows for the hybridization of complex bioactive and fluorescent-labeled carboxylic acids with diaryliodonium(III) salts.
Keywords: auxiliary ligand; diaryliodonium(III) salts; hybridization; hypervalent iodine; organocarboxylates